Interannual variations of the North Equatorial Current/Undercurrent from mooring array observations - Huang, Ying; Zhang, Linlin; Wang, Fujun; Wang, Fan; Hu, Dunxin (Frontiers in Marine Science, 2022)
Interannual variability of the North Equatorial Current (NEC)/Undercurrent (NEUC) in the northwestern Pacific was investigated with the mooring array measurements at 130°E during 2014-2021, in combination with the satellite altimetry. Mooring observations indicate that the velocity of the NEC/NEUC in the upper 900 m exhibits significant variations on the interannual time scale. The westward-flowing NEC strengthens when the underlying eastward-flowing NEUC weakens, and the NEUC branch at 8.5°N is intensified during the mature phase of El Niño and reaches the maximum velocity during the decay phase of El Niño. The phase of the interannual variation of the currents delays with the increasing latitude, with the signal at 15°N lagging that at 8.5°N by about one year. Based on a 1.5 layer reduced gravity model, the interannual variation is suggested to be controlled mainly by the westward propagating baroclinic Rossby wave induced by the wind stress curl forcing in the central Pacific. Different propagating speed of the baroclinic Rossby wave at different latitudes explains the meridional phase lag of the interannual signal. Empirical Orthogonal Function and vertical mode decomposition analysis suggest that the interannual variation of the NEC/NEUC velocity in the northern part is dominated by surface-intensified signals with a vertical structure of the first baroclinic mode, while that in the southern part is dominated by subsurface-intensified signals which is associated with the combination of the first two baroclinic modes. The low-order mode baroclinic response of the ocean to the wind forcing accounts for the interannual fluctuation of the NEC/NEUC velocity observed by the mooring array.